Peningkatan Hasil Belajar Akidah Akhlak Materi Aliran dan Tokoh Ilmu Kalam melalui Metode Snowball Throwing di Madrasah Aliyah Salafiyah Kota Cirebon - Istijabah (Jurnal Pendidikan Madrasah, 2021)
This study aims to improve the learning outcomes of Akidah Akhlak through the Snowball Throwing Method. The subject of the study was a grade XI IPA 1 MA Salafiyah Cirebon student in the 2017/2018 school year. This study uses the Class Action method through two cycles. Data is collected through tests, observations, and documentation. The results showed that from the pre-cycle process, cycle I, and cycle II experienced a significant increase. Pre-cycle and cycle I results were at 45.7% percentage, increasing to 97.1% in cycle II. While the average grade value has an average score of 72.4 on pre-cycle, 74.9 on cycle I, and 90.7 on cycle II. Snowball throwing method can improve students' learning outcomes in MA Salafiyah Cirebon.